Insights into the drivers of histopathological changes and potential as bio-indicator of riverine health of an aquatic apex predator from a premier conservation area: A multiple lines of evidence and multivariate statistics approach. (January 2017) - Gerber, R.; Wagenaar, G.M.; Smith, W.; Ikenaka, Y.; Smit, N.J.
Highlights: The first study examining the fish health status of tigerfish from Kruger National Park. Histopathological changes were present but indicated fish were in good health. Multivariate analysis indicated changes differed both spatially and temporally. Metals rather than OCPs were shown to be drivers of histopathological changes found. Multiple lines of evidence approach validated tigerfish as viable bio-indicators. Abstract: There is a need for sensitive bio-monitoring and indicator tools in toxicant impact assessment to show the effect on fish health. Histopathological assessment of fish tissue is a bio-monitoring tool allowing for early warning signs of disease and detection of long term injury in cells, tissues or organs. The aims of this study were firstly to determine and compare the health status of the tigerfish ( Hydrocynus vittatus ) from two lowland rivers in Kruger National Park (KNP), secondly to attempt to explain the histological changes observed, through the application of a suite of multivariate statistics to relate changes to biotic levels of selected metals and organochlorine pesticides (OCPs) and thirdly to determine the suitability of H. vittatus as a bio-indicator of riverine health. Tigerfish were caught using rod and reel from the Olifants (n = 37) and Luvuvhu Rivers (n = 34) between 2009 and 2011. The histology-based fish health assessment (liver, kidney, gills and gonads) indicated that fish were in relatively good health. Even though fish were considered to be healthy, the general fish health in both rivers improved over time, corresponding to an overall decrease in river pollution, most notably in terms of metals. The incorporation of multiple lines of evidence in tigerfish, including histopathological changes and organ and whole organism indices, proved to be a valuable tool in using a bio-indicator approach toward river monitoring. These histopathological changes serve as an early warning system to more serious health concerns arising if the pollution in the rivers of the KNP is not dealt with. The use of a suite of uni- and multivariate statistics proved helpful in determining the links between fish health and river contamination and further proved to be a valuable tool in assessing spatial and temporal differences in river pollution and the effects thereof on the selected bioindicator.